Financial performance analysis of DSE listed Shariah-based Islami banks in Bangladesh - Al Faruque, Abdullah; Faruque, Md. Omar; Habibullah, Mohammad (International Journal for Multidisciplinary Research (IJFMR), 2023)
The aim of this paper is to show the impact of selected firm specific factors on the performance Dhaka Stock Exchange- DSE listed Sharia-based Islamic banks of Bangladesh. The quantitative research method STATA 14.2 is used in this study. Secondary panel data of 5 Banking Companies spanning from 2016 to 2022 (35 observations) has been used for this study. The Return On Assets serves as the dependent variable, whereas Investment Deposit Ratio, Capital Adequacy Ratio, Classified Investment to total Investment, Inward remittance, and Cost of Fund serves as independent variables. Pearson’s correlation matrix, ordinary least square regression, and a few econometrics tests have been employed for the analysis purpose. The empirical results found that inward remittance has significant and positive association with the changes in Return on Assets. All other explanatory variables other than Classified Investment to total Investment have positive but insignificant impact on the changes in the explained variable. All the econometrics tests for testing the fitness of the OLS regression model advocate that the developed regression model is fit.